2018
DOI: 10.1016/j.jmb.2018.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics of the Activation of Elongation Factor 2 Kinase by Ca2+-Calmodulin

Abstract: Eukaryotic elongation factor 2 kinase (eEF-2K), the only known calmodulin (CaM)-activated α-kinase, phosphorylates eukaryotic elongation factor 2 (eEF-2) on a specific threonine (Thr-56) diminishing its affinity for the ribosome and reducing the rate of nascent chain elongation during translation. Despite its critical cellular role, the precise mechanisms underlying the CaM-mediated activation of eEF-2K remain poorly defined. Here, employing a minimal eEF-2K construct (TR) that exhibits activity comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(63 citation statements)
references
References 66 publications
9
52
2
Order By: Relevance
“…Using native mass spectrometry, we had previously demonstrated that CaM and TR form a high‐affinity heterodimeric complex of molecular weight of ~77.3 kDa in the presence of Ca 2+ . Given the size of the CaM•TR complex and its low stability even at modest concentrations (~50 μM) over extended periods of time, we took advantage of the excellent sensitivity provided by methyl groups for NMR in large, proton‐sparse systems .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using native mass spectrometry, we had previously demonstrated that CaM and TR form a high‐affinity heterodimeric complex of molecular weight of ~77.3 kDa in the presence of Ca 2+ . Given the size of the CaM•TR complex and its low stability even at modest concentrations (~50 μM) over extended periods of time, we took advantage of the excellent sensitivity provided by methyl groups for NMR in large, proton‐sparse systems .…”
Section: Resultsmentioning
confidence: 99%
“…The 20 Ile residues on TR (Figure S2A,S2B) are distributed over all its functional domains including the N‐terminal CBD (Ile89, that constitutes the fifth position of 1–5–8–14 binding mode seen in the structure of the Ca 2+ ‐CaM•eEF‐2K CBD complex), on the N‐lobe of the kinase domain (Figure S2A; KD N ; Ile107, Ile131, Ile173, Ile214, Ile215, and Ile232), the C‐lobe of the kinase domain (Figure S2A; KD C ; Ile209, Ile237, Ile251, Ile271, Ile275, Ile287, and Ile317), on the loop connecting the N‐ and C‐terminal regions of TR (a remnant of the R‐loop; Ile349 that lies next to Thr348, the site of primary activating autophosphorylation) and on the CTD (Figure S2B; Ile518, Ile522, Ile567, Ile581, and Ile614). Of these 20 resonances, 15 were unambiguously assigned using a mutation‐based approach as described previously (see Figure S3 for examples that illustrate this approach).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is worth mentioning that PDGF-BB-mediated activation of the eukaryotic elongation factor 2 kinase (eEF2K), also named CaMK-III, which is negatively regulated by CaM [157] (reviewed in [158]), enhances the proliferation and migration of VSMCs. This works via the ERK/MAPK, p38MAPK, Akt pathways, and Hsp27 as a downstream substrate of p38MAPK, shown by results using the eEF2K inhibitor A-484954 [159].…”
Section: Cam-dependent Phosphorylationmentioning
confidence: 99%